PERBANDINGAN EFEKTIVITAS JERAPAN Pb DALAM PARTIKULAT OLEH POHON TANJUNG (Mimusops elengi) DAN POHON BUNGUR (Lagerstroemia) (STUDI KASUS DI JALAN TIMOHO YOGYAKARTA) - Sunarsih, Sri; Suseno, Hadi Prasetyo; Fajri, Muhammad Aulia (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2021)
The ability of plants to absorb metallic pollutants varies. The research has been conducted to compare the effectiveness of Tanjung (Mimusops elengi) and Bungur (Lagerstroemia) plants in absorbing Pb metal in particulate matter. The effect of location and leaf height on the effectiveness of pollutant uptake was also observed. Sampling was carried out in July 2020-September 2020 by taking leaves that were not too dark or light in color. Leaves taken at heights 3, 6, and 9 m on Timoho side Street. The particulate and leaf samples were digested and then analyzed their Pb levels using an Atomic Absorption Spectrophotometer (AAS). The results showed that the Tanjung plants with denser leaves captured more particulate deposits than the Bungur plants. This plant is also more effective at absorbing and accumulating Pb metal, which is indicated by the ratio of Pb metal in the leaves to Pb in particulates which is higher than the Bungur plant. These results were consistent for each sampling period, at each location and each crown height.